Integrity Constraints Maintenance For Parallel Databases - Ahmad Hamed Hanandeh, Feras (2006)

(untitled)
This research work proposed a standard framework for maintaining integrity in parallel database systems. A model consisting of two main modules has been successfully implemented. This framework is flexible and can be extended easily as the framework is designed in a modular fashion where each module has a clear function, input and output and interacts easily with the other modules.